Surgical treatment of ectopic adrenocorticotropic hormone syndrome with intra-thoracic tumor - Zhou, Xiang; Hang, Junbiao; Che, Jiaming; Chen, Zhongyuan; Qiu, Weicheng; Ren, Jian; Yang, Xiaoqing; Xiang, Jie; Li, Hecheng (Journal of Thoracic Disease; Vol 8, No 5 (May 01, 2016): Journal of Thoracic Disease, 2016)
Background: The study was to review the clinical manifestations and laboratory examinations of ectopic adrenocorticotropic hormone (ACTH) syndrome, and to analyze the efficacy of surgical treatment. Methods: The clinical data, surgical therapy, and outcome of 23 cases of ectopic ACTH syndrome accompanied by intra-thoracic tumors were reviewed. The tumors were removed from all the patients according to the principles of radical resection. Results: The tumors were confirmed as associated with ectopic ACTH secretion in 19 cases. Hyperglycemia and hypokalemia were recovered, while plasma cortisol, plasma ACTH and 24-hour urinary free cortisol (UFC) levels were significantly reduced after surgery in these 19 cases. Recurrences of the disease were found in six cases during following-up, and five of them died. Conclusions: The thoracic cavity should be a focus in routine examinations of patients with symptoms of Cushing’s syndrome (CS), because ectopic ACTH-producing tumors are commonly found in bronchus/lung and mediastinum. Despite the incidence of the pulmonary nodule secondary to opportunistic infection in some cases, surgery is still the first choice if the tumor is localized. The surgical procedure should be performed according to the principles in resection of lung cancer and mediastinal tumor. The surgical efficacy is significant for short-term periods; however, the recurrence of the disease in long-term periods is in great part related to distal metastasis or relapse of the tumor.